Забезпечення номінальної потужності стаціонарного газового двигуна при використанні низькокалорійних газових палив - Марченко, Андрій Петрович; Осетров, Олександр Олександрович; Кравченко, Сергій Сергійович (НТУ "ХПІ", 2015)
Відмінність нижчої теплоти згоряння низькокалорійних газових палив від природного газу призводить до зміни протікання робочого процесу та потребує збільшених циклових подач до циліндру для отримання еквівалентної теплоти згоряння. В роботі проаналізовано можливості конструктивного забезпечення номінальної потужності двигуна з форкамеро-факельним запалюванням та якісним регулюванням потужності при використанні в якості палива різних низькокалорійних газів.

The difference between the net calorific value of low-calorie gas fuels from natural gas leads to a change in the working process and requires an increase in cyclic supply into the cylinder for the equivalent calorific value. This paper analyzes the possibilities of constructive ensure rated engine power to the precombustion chamber jet ignition and power quality control for use in a variety of low-calorie fuel gas. It is shown that the cyclic provide the necessary gas supply to the cylinders of the engine can be achieved by increasing the flow passages of parts of gas equipment, an increase in pressure in the gas supply system and gas equipment duplicated. With the engine on biogas and coke oven gas rated power provided the replacement of the gas equipment the engine equipment with larger flow passages. When using synthesis gas and coal gas expedient together with the replacement gas equipment on the apparatus with increased flow passages to increase the pressure of the fuel gas in the fuel system. In the case of pyrolysis and generator gases and rational use double gas installations with larger flow passages.
Support nominal power stationary gas engines when using the low calorie gas fuels
Keywords: НГП; двигуни внутрішнього згорання; шахтний газ; синтез газу; форкамерно-факельне запалювання